A data collection method based on extended wireless charging Qi standard - Bai Guanglei; Jiang Hao; Shi Jiawen; Jiang Wei; Zhang Qi (Dianzi Jishu Yingyong, 2018)
Wireless charging has the advantages of safe charging and high efficiency. It has been applied to wireless data acquisition systems to solve the problem of power energy life and prolong the working life of the system. However, wireless data acquisition systems based on wireless charging currently use additional wireless communication modules to transmit data collected by sensors, which increases the volume and power consumption of the sensor nodes. It is undoubtedly catastrophic in data acquisition applications such as implantable medical devices and volume-restricted confined containers. Considering the hybrid transmission of energy and data in wireless charging system, the Qi standard is expanded in this paper to realize the transmission of sensor acquisition data by means of wireless charging system. Without additional wireless communication module, this method reduces the volume and power consumption of sensor nodes, simplifies the system circuit and reduces the cost.